The attendance in full-time education Post-National Education Plan (PNE 2014-2024) in the Baixada Fluminense - Diniz Junior, Carlos Antonio (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The purpose of this article is to analyze the offer of full-time education in the municipal networks of Baixada Fluminense (Rio de Janeiro), after the National Education Plan (PNE) was approved, during the 2015-2019 period. Having a quantitative and qualitative nature, the study is based on theoretical references that discuss the regulation of full-time education in Brazil, the PNE and the Municipal Education Plans (PMEds). Also, enrollment data from the School Censuses of the period allowed us to analyze the evolution of Goal 6 of the PNE in the region. Among its main results, it is possible to observe different scenarios  to the provision of full-time in early childhood education and elementary education. It is also noteworthy that the absence of wide articulation between the federated entities and the discontinuity of policies, on the part of the federal government, contributed to the significant drop in enrollments in full-time, particularly in elementary education.